2007
DOI: 10.1002/nau.20457
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to lower urinary tract symptoms among a sample of employed women in Taipei

Abstract: Aim: To identify factors associated with lower urinary tract symptoms (LUTS) among female elementary school teachers in Taipei. Methods: This study is a cross-sectional, descriptive study. A total of 520 surveys were distributed to 26 elementary schools in Taipei. Logistic regression was used to identify possible factors related to individual LUTS. Results: Study results were based on the information provided by 445 participants. Of the 445 teachers, 293 (65.8%) experienced at least one type of LUTS. Factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Namely, high prevalence of concomitant OAB is thought to be one of the characteristics among constipation predominant FD patients. Previous studies also showed that there is a significant overlap between lower urinary tract symptoms and constipation 5,22,23 . Charach et al.…”
Section: Discussionmentioning
confidence: 95%
“…Namely, high prevalence of concomitant OAB is thought to be one of the characteristics among constipation predominant FD patients. Previous studies also showed that there is a significant overlap between lower urinary tract symptoms and constipation 5,22,23 . Charach et al.…”
Section: Discussionmentioning
confidence: 95%
“…More recent research, particularly among men, has associated the metabolic syndrome with LUTS; hyperinsulinaemia, obesity, noninsulin-dependent diabetes, dyslipidaemia, and hypertension were found to be associated with an increased risk of BPH [4,7,8]. Given that many of the comorbid conditions noted are modifiable by increased physical activity and weight loss, it is not surprising that low levels of physical activity and elevated body mass index (BMI) are well-documented risk factors for LUTS in men and women [1,3,6,[9][10][11][12]. Research on smoking as a risk factor for LUTS has been inconclusive, with the finding that current smokers are at greater risk of LUTS than are former smokers or nonsmokers [4,6,13], and conversely reports of either no association or a possible inverse relationship between cigarette smoking and LUTS [2,4,14].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is often blamed to exacerbate OAB symptoms, so patients are usually advised to avoid caffeine consumption. [3–5] For those OAB patients who are coffee lovers, avoiding coffee and coffee products can equally hurt their quality of life, and they may wonder if caffeine actually has anything to do with their OAB symptoms at all.…”
Section: Introductionmentioning
confidence: 99%